Interactive Multimedia Development of Aircraft Safety System Based on Adobe Flash - Agus Suryo Wibowo (SENATIK STT Adisutjipto, 2018)
The understanding of safety needs to be emphasised to every Airman. Therefore, it is necessary to develop an Aircraft Safety application utilising interactive and interesting multimedia which able to helps not only pilots but also ground crew in understanding safety subject mentioned. Development of Aircraft System application based on Adobe Flash displays 4 (four) option menu as follows general information, subject, quiz, and biography. User also able to assess their understanding of Aircraft Safety subject utilising quiz menu that displays their score. Aircraft Safety functionality test using black box testing yielded excellent result. Aircraft Safety application evaluation was done by conducting direct test and survey which involve 30 students of Air Force Flying School with 3 (three) assessment which are effectivity, efficiency, and satisfaction. User agreed and gave average score for each aspect as follows 4.63 for effectivity, 4.53 for efficiency, and 4.52 for satisfaction with the scale of 1 to 5.